Efficacy and safety of blinatumomab in children with relapsed/refractory B cell acute lymphoblastic leukemia: A systematic review and meta-analysis - Chen, Bin; Zou, Zhuan; Zhang, Qian; Chen, Kexing; Zhang, Xiaoyan; Xiao, Dongqiong; Li, Xihong (Frontiers in Pharmacology, 2023)
Several clinical trials have been conducted to evaluate the effects of blinatumomab in childhood B-cell acute lymphoblastic leukemia (B-ALL). We conducted this meta-analysis to validate the efficacy and safety of blinatumomab in pediatric patients with relapsed/refractory B-ALL (R/R B-ALL). We searched and investigated all relevant studies in the PubMed, Web of Science, Embase, and Cochrane Library databases. The primary outcomes were complete response (CR), overall survival (OS), event-free survival (EFS), minimal residual disease (MRD) response, allogeneic hematopoietic stem cell transplantation (allo-HSCT) and were calculated separately for randomized controlled trials (RCTs) and single-arm studies. The secondary end points were adverse effects (AEs) and the relapse rate. The Cochrane, bias assessment tool, was used to assess the risk of bias in RCTs. The methodological quality of single-arm studies was assessed using the methodological index for non-randomized studies (MINORS) tool. The meta-analysis included two RCTs and 10 single-arm studies, including 652 patients in total. Our study showed that in the single-arm studies, the combined CR rate was 0.56 (95% confidence interval (CI): 0.45–0.68), the odds ratios (ORs) of OS was 0.43 (95% CI 0.32–0.54), the EFS rate was 0.30 (95% CI: 0.20–0.40), the MRD response was 0.51 (95% CI: 0.34–0.68), allo-HSCT rate was 0.62 (95% CI: 0.50–0.74), the AE rate was 0.65 (95% CI: 0.54–0.76) and the relapse rate was 0.32 (95% CI: 0.27–0.38). In the RCTs, the blinatumomab-treated group compared with the chemotherapy group had a combined OS rate of 0.12 (95% CI: 0.05–0.19) and an EFS rate of 2.16 (95% CI: 1.54–3.03). The pooled MRD response rate was 4.71 (95% CI: 2.84–7.81), allo-HSCT was 3.24 (95% CI: 1.96–5.35), the AE rate was 0.31 (95% CI: 0.16–0.60), and the relapse rate was 0.69 (95% CI: 0.43–1.09). According to this meta-analysis, blinatumomab shows potent therapeutic efficacy and limited AEs in children with R/R B- ALL